Hill-starting a heavy haul train with a 24-axle locomotive. (March 2022) - Wu, Qing; Yang, Xiangjian; Jin, Xihong
Head-end trains are more efficient than Distributed Power trains in terms of train marshalling. This paper studied an unprecedent real-world engineering problem to hill-start a long heavy haul train at a 1.2% up-hill gradient by using a 14400 kW 24-axle AC electric locomotive (maximum traction force 2280 kN). Longitudinal Train Dynamics simulation were conducted to assess five potential driving strategies in terms of train speed and in-train forces. The simulation results show that the locomotive can hill-start the heavy haul train with 80% traction throttle. However, maximum locomotive coupler forces (1840 kN) exceeded coupler knuckle yield strength (1780 kN) of the original coupler system design. Sensitivity analyses were conducted to assess the implications of train starting resistance for train speeds and in-train forces. The study recommends increasing coupler knuckle yield strength to 2450 kN. The increased knuckle yield strength is still lower than that of the chassis, which is able to meet system design requirement; it also enables the locomotive to hill-start by using traction throttles of 80, 90, and 100% with safety factors of 1.3, 1.2 and 1.1 respectively.